Islamic Ethics of War: A Comprehensive Examination of Just War Principles in Islamic Jurisprudence - Muhammed Amirshazin. K (Al-Mahkamah: Islamic Law Journal, 2025)
This article comprehensively examines the Islamic ethics of war, a sophisticated framework deeply rooted in the Quran and Sunnah, often misunderstood as advocating unbridled violence. It delves into the foundational principles that prioritize humanitarian considerations, proportionality, and moral restraint in armed conflict. We explore how classical Islamic jurisprudence, through the works of scholars like Al-Sarakhsi and Ibn Rushd, meticulously codified rules for just cause, legitimate authority, and non-combatant protection, often predating modern international humanitarian law. The article demystifies the multifaceted concept of jihad, clarifying its defensive nature and broader spiritual dimensions. It also analyzes the contemporary relevance and application of these ethics in modern warfare, including challenges posed by cyber warfare and drone technology. Finally, it challenges pervasive misconceptions, emphasizing how authentic Islamic scholarship consistently promotes peace, justice, and strict ethical conduct, offering crucial insights for global conflict resolution.